New paradigms in venous thromboprophylaxis of medically ill patients - Spyropoulos, Alex C.; Raskob, Gary E. (Thrombosis and Haemostasis, 2017)
Acutelly-ill hospitalised medical patients are at risk of venous thromboembolism (VTE), both in-hospital and in the immediate post-discharge period, and mortality from VTE is thought to be particularly high in this patient population. However, despite previous mandates from international antithrombotic guidelines such as those of the American College of Chest Physicians (ACCP) for the “universal” use of thromboprophylaxis in hospitalised medical patients, global audits suggest that implementation of thromboprophylaxis continues to be challenging because of the perceived higher risk of bleeding and lower risk of VTE than that reported in clinical trials. Recent population-based studies also reveal that a “universal” hospital-only thromboprophylactic strategy does not reduce the community burden of VTE from this population, which may constitute nearly one quarter of the attributable risk of VTE. Lastly, four large randomised placebo-controlled trials of extended thromboprophylaxis have failed to show a definitive net clinical benefit in hospitalised medical patients. Recent large-scale efforts in deriving and validating scored VTE and bleed risk assessment models (RAMs) have been completed in the medically-ill population. In addition, an elevated D-dimer as a new biomarker to identify at-VTE risk medically ill patients has also undergone prospective evaluation. This paper will review current concepts of VTE and bleed risk in hospitalised medical patients, both in the hospital as well as the post-hospital discharge period, and will discuss new paradigms of thromboprophylaxis in this population using an individualised, patient-centered approach.
Keywords: Medical patient; risk assessment models; d-dimer; venous thromboembolism; bleeding; thromboprophylaxis; Padua Score; NHS Tool; IMPROVE Score; low-molecular-weight heparin; direct oral anticoagulants